2009
DOI: 10.1039/b813871k
|View full text |Cite
|
Sign up to set email alerts
|

Determination of hydroxyl rate constants by a high-throughput fluorimetric assay: towards a unified reactivity scale for antioxidants

Abstract: We describe in this article the development of a new method for the determination of rate constants of reaction of the hydroxyl radical, generated by radiolysis of water, with almost any possible molecule. It has been designed to provide a fast and reliable screening of antioxidant banks using microplates. Our particular approach is based on the use of the coumarin molecule as a competitor against the tested molecules: after a fast pulse of low dose irradiation, the fluorescence of 7-hydroxycoumarin produced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…32.5 nm nanoparticles were put in the presence of coumarin to measure the hydroxyl radical production after irradiation as it was suggested to be the main radical responsible for target degradation when nanoparticles are irradiated by ionizing radiation . Among the numerous ways of quantifying hydroxyl radical production, the coumarin HO • trapping assay was chosen because it is fully compatible with nanoparticles as it doesn' induce any aggregation and because fluorescence detection that can be run is a very sensitive technique allowing the detection of quantities down to 30 n m of hydroxyl radical …”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…32.5 nm nanoparticles were put in the presence of coumarin to measure the hydroxyl radical production after irradiation as it was suggested to be the main radical responsible for target degradation when nanoparticles are irradiated by ionizing radiation . Among the numerous ways of quantifying hydroxyl radical production, the coumarin HO • trapping assay was chosen because it is fully compatible with nanoparticles as it doesn' induce any aggregation and because fluorescence detection that can be run is a very sensitive technique allowing the detection of quantities down to 30 n m of hydroxyl radical …”
Section: Resultsmentioning
confidence: 86%
“…[ 14 ] Among the numerous ways of quantifying hydroxyl radical production, the coumarin HO • trapping assay [18][19][20] was chosen because it is fully compatible with nanoparticles as it doesn't induce any aggregation and because fl uorescence detection that can be run is a very sensitive technique allowing the detection of quantities down to 30 n m of hydroxyl radical. [ 21 ] Louit et al performed HO • quantifi cation by titration of 7-hydroxycoumarin that was shown to be the main fl uorescent product of coumarin oxidation. This titration was validated both by liquid chromatography coupled to fl uorescence detection and by fl uorescence titration without preliminary separation of the oxidized coumarin derivatives.…”
Section: Coumarin Assay Adaptedmentioning
confidence: 99%
“…The second order rate constants for the reaction of HO· with a variety of biologically relevant molecules are typically near the diffusion-controlled limit (>10 9 M −1 s −1 ), indicating that very few collisions are required for a reaction to occur. 28 Thus, it will be expected that biological damage by HO· will be localized to its site of generation, which in many cases means the site where a catalytic metal is present (reaction 13). In fact, evidence suggests that under certain conditions “free” HO· is not generated in the Fenton reaction but that rather a metal-bound oxidant is made, and this is the ultimate oxidant.…”
Section: Biological Chemistry Of Dioxygen (O2) and Related Speciesmentioning
confidence: 99%
“…That is in principle also possible using computational methods [232, 233], but it would be rather tedious and expensive to carry out such calculations for a large number of different enzymes and reactions. There is hope, however, that this may not be necessary given recent efforts to obtain kinetic rate constants in a high-throughput and consistent manner that should result in more reliable data [234, 235]. …”
Section: Towards Comprehensive Cellular Modelsmentioning
confidence: 99%